Kewenangan Desa Dalam Menangani Konflik Jual Beli Tanah (Studi Berdasarkan Undang-Undang Nomor 6 Tahun 2014 di Desa Kembang Mekar Sari - Jusnaidi; Jamri; Kms. Novyar Satriawan Fikri (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
The authority of the Village Government in resolving land purchase conflicts among village communities in Kembang Mekar Sari Village, Indragiri Hilir Regency, is based on Law Number 6 of 2014 concerning Villages. The research questions include the regulation of village authority, the constraints in handling land purchase conflicts, and the village government's efforts to resolve these conflicts. The research used a sociological legal research approach with a descriptive analytical approach. Data were obtained through interviews with the Village Head, village officials, community leaders, and a literature review of laws and legal literature. The results indicate that the Village Government plays a role as a mediator in resolving land purchase conflicts through deliberation and a family approach. However, the implementation of this authority is not optimal due to the absence of a Village Regulation specifically governing the mechanism for resolving land conflicts. The obstacles faced include poor community land administration, limited village authority, and a lack of community legal understanding. The village government's efforts include mediation, land law socialization, land administration restructuring, and plans to establish a Village Regulation concerning community dispute resolution.